Basic human needs and nursing care dependency of institutionalized elders - Rocha, Luanna dos Santos (2013)
ABSTRACT The objective of this study was to identify the basic human needs and the level of dependency on nursing care presented by institutionalized elders. This observational, quantitative and descriptive study was performed with 67 elder inpatients of a Geriatric Long-Term Care Institution in Maceió, Alagoas, Brazil. Data collection was performed using an instrument containing data regarding the institution’s and subjects’ characteristics as well as the Patient Classification System. Results show a predominance of male patients, older than 70 years, illiterate, single, and living in the institution for approximately 5.5 years. The most affected basic human needs were: body care, health education, locomotion, elimination, and mobility. A degree of partial dependency on nursing care was the most commonly observed. Results permit a better understanding of the true needs of institutionalized elders and collaborate with the (re)organization of nursing care. Descriptors: Aged; Geriatric Nursing; Homes for the Aged.